Reactive oxygen species-responsive RNA interference - Rühle, Jennifer; Klemt, Insa; Abakumova, Tatiana; Sergeeva, Olga; Vetosheva, Polina; Zatsepin, Timofei; Mokhir, Andriy (Chemical Communications, 2022)
Due to oxidative instability, arylboronic acids are not compatible with the solid-phase synthesis of nucleic acids. We solved this problem and, based on these findings, developed siRNA prodrugs activated in the presence of reactive oxygen species (ROS) in vivo. These prodrugs can be used for specific targeting of ROS-rich cancer cells.
CRIS-Team WoS Importer:2022-04-01

Red light-triggered photoreduction on a nucleic acid template - Dutta, Subrata; Rühle, Jennifer; Schikora, Margot; Deussner-Helfmann, Nina S.; Heilemann, Mike; Zatsepin, Timofei; Duchstein, Patrick; Zahn, Dirk; Knoer, Guenther; Mokhir, Andriy (Chemical Communications, 2020)
Conjugate Sn(iv)(pyropheophorbide a)dichloride-(peptide nucleic acid) catalyzes reduction of azobenzene derivatives in the presence of complementary nucleic acid (NA) upon irridiation with red light (660 nm). This is the first red light-induced NA-templated photoreduction. It is highly sensitive to single mismatches in the NA-template and can detect down to 5 nM NAs.
CRIS-Team Scopus Importer:2020-09-11

Triggering RNA Interference by Photoreduction under Red Light Irradiation - Rühle, Jennifer; Klemt, Insa; Mokhir, Andriy (Molecules, 2023)
RNA interference (RNAi) using small interfering RNAs (siRNAs) is a powerful tool to target any protein of interest and is becoming more suitable for in vivo applications due to recent developments in RNA delivery systems. To exploit RNAi for cancer treatment, it is desirable to increase its selectivity, e.g., by a prodrug approach to activate the siRNAs upon external triggering, e.g., by using light. Red light is especially well suited for in vivo applications due to its low toxicity and higher tissue penetration. Known molecular (not nanoparticle-based) red-light-activatable siRNA prodrugs rely on singlet oxygen (1O2)-mediated chemistry. 1O2 is highly cytotoxic. Additionally, one of the side products in the activation of the known siRNA prodrugs is anthraquinone, which is also toxic. We herein report on an improved redlight-activatable siRNA prodrug, which does not require 1O2 for its activation. In fact, the 5′ terminus of the antisense strand is protected with an electron-rich azobenzene promoiety. It is reduced and cleaved upon red light exposure in the presence of Sn(IV)(pyropheophorbide a)dichloride acting as a catalyst and ascorbate as a bulk reducing agent. We confirmed the prodrug activation upon red light irradiation both in cell-free settings and in human ovarian cancer A2780 cells.
CRIS-Team Scopus Importer:2023-06-09
Keywords: azobenzene; photoreduction; promoiety; red light activation; RNAi; selective cancer targeting; siRNA prodrug